The Contemporary Brazilian Pandeiro: Confluences between Worlds - Biagioni, Vitor Lyra (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2025: Anais Estendidos do XIX Simpósio Brasileiro de Computação Musical, 2025)
This article has no abstract.